Variants of self-assembling peptide, KLD-12 that show both rapid fracture healing and antimicrobial properties. (July 2015) - Tripathi, Jitendra K.; Pal, Subhashis; Awasthi, Bhanupriya; Kumar, Amit; Tandon, Anshika; Mitra, Kalyan; Chattopadhyay, Naibedya; Ghosh, Jimut Kanti
Abstract: KLD-12 (KLD) is a 12-residue self-assembling peptide that can adopt nano-structures and is known for its tissue-engineering properties. Our objective was to introduce antimicrobial attribute to KLD which would help in preventing secondary infection associated with external application of such tissue engineering materials. Considering the net charge of KLD-12, varying number of cationic arginine residues were added to its N-terminus. KLD variants showed appreciable bactericidal properties without any significant increase in cytotoxicity against tested mammalian cells. Further, these variants adopted β-sheet structures and self-assembled into nano-structures comparable to that of KLD. Interestingly, the KLD variants with two (KLD-2R) and three (KLD-3R) arginine residues added to its N-terminus showed significant osteogenic effect which was comparable or better than the original peptide as evident from the alkaline phosphatase activity assay, mineralized nodule formation and expression of different osteogenic genes. Particularly, application of KLD-2R in rats to the site of a drill-hole (0.8 mm diameter) that was created in the femur metaphysis displayed significantly higher bone regeneration compared to that of KLD. The results demonstrate a simple way to improve biological property of a self-assembling peptide with tissue engineering property.